Taxonomy and multi-gene phylogeny of Micropsalliota (Agaricales, Agaricaceae) with description of six new species from China - Yan, Jun-Qing; Zeng, Zhi-Heng; Hu, Ya-Ping; Ke, Bin-Rong; Zeng, Hui; Wang, Sheng-Nan (Frontiers in Microbiology, 2022)
Micropsalliota is a relatively small genus containing only 62 previously identified species. Here, we describe six new taxa of Micropsalliota based on morphological and phylogenetic analyses: M. minor, M. ovalispora, M. pseudodelicatula, M. rufosquarrosa, M. tenuipes, and M. wuyishanensis and a new record taxon to China. The first Maximum likelihood and Bayesian analyses of a three-gene dataset (ITS, LSU, and rpb2) separated the genus into 18 weakly to strongly supported major clades and subclades, but only a few subclades were synapomorphies. According to phylogenetic analyses, M. cornuta does not belong in Micropsalliota. A key to 20 species of Micropsalliota in China is provided.